A Model for Implementation of Intelligent Business Solutions on the Basis of the Level of BI Maturity: An Iranian experience (2019)
The purpose of this research is to provide a basis for choosing the approach to implementing business intelligence systems based on the maturity of the organization. This research not only recommends considering the level of business intelligence maturity while planning for the implementation, but also recommends the use of IT governance levers in order to increase the level of efficient usage of such systems. In this research, while analyzing the subject by experts in the Delphi Fuzzy method, these ideas have been reviewed and verified in nearly 109 organizations responding to the questionnaires. The result of this research is a fuzzy inference engine that suggest the best execution package required, by entering data on the size and maturity of the organization. Packages containing the appropriate implementation methodology, products at that maturity level and, consequently, IT governance processes and requirements to that level of maturity.